Constraints on the Global War on Terror in the Post Cold War Era - Ogirai, John Chrysestom (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
In this paper the author aspires to profile the difficulties involved in the war against terrorism in the post cold war era. Terrorism has become a very topical issue in the world. The world today is threatened with extinction due to the threat posed by terrorism. Terrorism is a age-less phenomena, which has began to exhibit a new energy and a new dimension. The frequency of which terror attacks occur every day, shows that terrorists are moving far ahead of government that are posed on curtailing their activities. Defeating terrorism in the near future might not be easy, despite various regional and international conventions against terrorism. The finding of this paper is that, there is no universally accepted definition of terrorism. The term terrorism is one of the most emotive and subjective words in the English language. Any attempt to define terrorism will be predicated on the assumption that, some classes of political violence are justifiable whereas others are not. Terrorism is a noticeable language; capable of creating fear and alarm to gain attention. The paper equally reveals that, two decades ago terrorists’ motives were associated with nationalism and separatism and leaned towards revolutionary and cold war ideological zeal. Today, there are greater complexity, diversity and unpredictability, due to the fact that suicide bombers have committed terrible acts in different parts of the globe. The finding of this paper is that, many terrorist organisations traffic in humans, computer chips, nuclear material, toxic wastes explosives and drug. Also, different types of terrorism are in existence and each of them is unique to the present time, namely, state sponsored terrorism, mass causality terrorism, chemical and super terrorism. States without ballot-box democracy and states with constitutional frameworks are at risk from terrorism. The paper concludes by stating that terrorism poses a big challenge to democracies and counter-terrorism legislations and force cannot end terrorism.